Material Waste Minimisation Strategies among Construction Firms in South-South, Nigeria - Adewuyi, Timothy Olubanwo; Odesola, Isaac Abiodun (International Journal of Sustainable Construction Engineering and Technology, 2016)
This study examined material waste minimisation strategies practiced by construction firms in the study area, the amount of waste generated and the relationship between them. The data collected were analysed using mean score, Spearman Rank Correlation, Kruskal-Wallis H and Mann-Whitney U tests. It is revealed that the most commonly employed strategies are “ensuring that storage facilities are properly secured before staff leave on a daily basis”; “checking of deliveries for any shortages and/or damages”; and “using materials before expiry date” with mean scores of 4.46, 4.22, 4.20 respectively. A significant variation in the level of material waste generated by different category of firms was confirmed. There is also a significant relationship between the level of minimisation strategies adopted and the waste generated. Based on the R2 values, 18.8% to 49.4% of the material waste generated for all the material types studied could be explained by the material minimisation strategies adopted on site except for stone base with 9.4%. %. The study recommends that the players in the industry should step up efforts towards introducing incentives to motivate labour to minimise material wastage on site and the use of modular design system.